Electrophysiological Abnormalities Associated With Sustained Attention in Children With Attention Deficit Hyperactivity Disorder and Autism Spectrum Disorder - Jiajing Zhao; Mengyi Bao; Wencong Ruan; Rui Kuang; Haifeng Li; Yueming Wang; Lin Yao (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
This study investigates electrophysio- logical abnormalities in children with Attention-Deficit/ Hyperactivity Disorder (ADHD) and Autism Spectrum Disorder (ASD) during sustained attention tasks, focusing on vigilance and inhibitory control, and explores associations between neural markers and attentional performance.Children with ADHD (n = 30), ASD (n = 23), and typically developing (TD) children (n = 31) completed a Test of Variables of Attention (TOVA) task while electroencephalography (EEG) was recorded. Event-related potentials (ERPs: P1, N2, P3) and event-related desynchronization/synchronization (ERD/ERS: theta ERS, alpha ERD, beta ERS) were measured and compared across groups. Correlations between electrophysiological features and behavioral performance were analyzedBoth ADHD and ASD groups demonstrated attenuated P1 amplitudes during vigilance task and reduced prefrontal theta ERS during inhibitory control. The ASD group exhibited additional impairments, including attenuated N2 amplitudes in inhibitory control, reduced P3 amplitudes, and weaker alpha ERD across conditions. The ADHD group showed additional deficits in theta ERS. Notably, N2 amplitude and theta ERS during vigilance state significantly correlated with response time measures. Children with ADHD and ASD share deficits in primary visual stimulus processing and inhibitory attention allocation. ASD-specific impairments involve top-down processing and inhibition, while ADHD-specific challenges involve attentional allocation and modulation. These findings enhance the electrophysiological understanding of sustained attention in ADHD and ASD, offering insights that may inform future diagnostic and intervention strategies.